Opioid Prescribing at Discharge in Opioid-Naïve Trauma Patients. Issue 1 (January 2023) - Johnston, Jackie P.; LaPietra, Alexis M.; Elsawy, Osama A.; Wang, Antai; Richards, Lynette M.; Yee, Stephanie; Foran, Lindsey A.; Hlayhel, Ahmad F.; Fahey, Ryan; Nerenberg, Steven F.
Background: Opioid analgesics remain mainstay of treatment for trauma-related pain despite growing concerns for opioid dependency or misuse. The purpose of this study was to evaluate opioid prescribing at hospital discharge after traumatic injury. Methods: This is a single-center, retrospective analysis of patients ≥18 years of age admitted for ≥24 hours with a primary diagnosis of traumatic injury. Those with alcohol use disorder, polysubstance abuse, chronic opioid use, or in-hospital mortality were excluded. The primary outcome was the incidence of patients prescribed opioids at discharge. Secondary outcomes included percent of patients who received nonopioids, intensive care unit (ICU) admission, and hospital length of stay (LOS). Results: Of the 927 encounters, 471 were included. The mean age was 60 ± 23 years, and 62.0% were male. The majority were blunt trauma, and 49.9% were falls. Mean initial injury severity score (ISS) was 9 ± 7.2. Of the 70.4% of patients prescribed opioids, 39.4% were discharged on opioids. Age ≥30 years, ICU admission, ISS <9, or Charlson Comorbidity Index >1 was less likely to have opioids prescribed at discharge. Most received nonopioids (93.6%) and multimodal analgesia (84.3%). The median hospital and ICU LOS were 5 (3-9) and 2 (0-4) days, respectively. Discussion: Only 39.4% had opioids prescribed at discharge. Opioid-reductive strategies may decrease in-hospital and discharge opioid prescribing. While opioid analgesics remain a mainstay of trauma-associated pain management, institution-wide opioid-sparing strategies can further reduce discharge opioid prescribing after trauma.